PENGARUH RETURN ON ASSET DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM KONTRUKSI PERUSAHAAN BUMN KHUSUS PADA PT ADHI KARYA (PERSERO) TBK - Meryati, Ani (RJABM (Research Journal of Accounting and Business Management), 2024)
This study intends to ascertain the impact of debt to equity ratio and return on assets on the share prices of state-owned construction companies, with a focus on PT Adhi Karya (Persero) Tbk, over the years 2014–2022. The Indonesia Stock Exchange website (www.web.idx.com) and the PT Adhi Karya (Persero) Tbk website provide the data for the quantitative method, which is processed using SPSS soft ware. Based on the research findings, it can be inferred that the variable Return On Assets (X1) partially influences stock prices (Y) with a tcount of 3.270 > ttable 2.447 and a significant value of 0.017 < 0.05. It can be inferred that the Debt to Equity Ratio (X2) variable partially has no significant effect on Share Prices (Y) based on the DER variable's tcount of 1.206 < ttable 2.447 with a significant value of 0.273 > 0.05. Furthermore, the F test findings showed that the ROA and DER variables jointly had a considerable impact on stock prices, with an Fcount value of 5.458 > Ftable 5.14 and a significant value of 0.045 < 0.05. Consequently, the construction share price of the BUMN company, namely PT Adhi Karya (Persero) Tbk, is significantly impacted by both the Return on Asset (X1) and Debt to Equity Ratio (X2) variables at the same time.